The Usage of Ear Acupressure in Gynecology and Obstetrics: A Systematic Review of Clinical Trials - Zahra Hadizadeh Talasaz; Talat Khadivzadeh; Mahboube Firoozi; Hoda Azizi; Morvarid Irani (Mashhad University of Medical Sciences, 2018)
Introduction: Ear Acupressure is a non-invasive and safe technique and is one of the approaches which can be used by doctors, midwives, nurses, and even patients themselves. Several studies have been conducted on ear acupressure in treatment of various diseases and problems of women. Therefore, the present study was conducted with aim to review the usage of ear acupressure on gynecology and obstetrics. Methods: In this review study, the articles indexed in databases of Pumped, Google scholar, Magiran, Irandoc, MEDLINE, Scoupus, and Web of Science were searched during 2006-2018 using the keywords based on MeSH including ear acupressure OR auriculotherapy by using AND with the keywords of dysmenorrhea, menopause, nausea and vomiting, constipation, low back pain, delivery, pregnancy, and infertility. The inclusion criteria included the insertion of search words in the title section and the articles' keywords in the clinical trials published in Persian and English. The articles which had used acupuncture and needles in combination were excluded from the study. The Jadad scale was used to assess the quality of the articles. Results: In this study, 12 clinical trials were reviewed. Out of three menopause-related articles, one had a significant effect with ear acupressure. Out of two dysmenorrhea-related articles, one showed a significant effect of ear acupressure on pain and negative emotions. Out of two labor pain-related articles, one reported significant effects of ear acupressure on pain relief. Out of two articles related to anxiety after cesarean section, one reported a significant reduction in anxiety. The article related to constipation also showed a significant improvement by using ear acupressure; no significant results were reported regarding nausea and infertility. Conclusion: Ear acupressure can be helpful in improving women's problems and is suggested as a complementary and alternative approach. However, due to the limited number of studies which were conducted in this area, as well as the limitation of some studies, it is recommended to perform further studies with removing the limitations and defects of previous studies before using it in clinical medicine.